The view of Islamic Law on Petalangan Malay Indigenous Peoples who Perform Inter-tribal Marriages - M Rivaldo; Desi Apriani; Heni Susanti; M Musa; Evi Yanti; Selvi Harvia Santri (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2021)
Abstract Purpose from research this is for knowing the view of Islamic Law on Sanctions given to the Malay Customary Society Adventurers who do Marriage A tribe. Method research used is ethod research A sociologist who is plunged research directly to field. Research this done in Perbatinan Region Balam Merah District Opponent. In the Qur'an and Hadith no found about obligations or forbid marriage a tribe Customs that exist in the tribe Malay about ban married a tribe this grounded above existing confidence regularly down hereditary from generation generation. Though customs Malay Adventure forbid marriage a tribe, however marriage the said no ever canceled and fixed considered valid marriage that has been done one quarter said. This indicate marriage a tribe not including illegal category. Because if a marriage banned then marriage the said should cancelled. Malay community Adventure consider marriage a tribe can However no good for done